Antimicrobial Properties of Green Disinfectant from Citrus Waste-Infused Used Cooking Oil Using Conventional Method - Miradatul Najwa Muhd Rodhi; Nur Affaaidil Amani Mohd Zaki; Harumi Veny; Fazlena Hamzah (Universitas Gadjah Mada, 2022)
This research aims to formulate a disinfectant from citrus waste-infused used cooking oil through the conventional process and evaluate its effectiveness in microbial elimination. Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography-Mass Spectrometry (GC-MS) were utilized to characterize citrus waste-infused used cooking oil. Two prominent bands belonging to the alkane (2921.93–2922.26 cm–1) and ester (1743.60–1743.73 cm–1) were observed on all FTIR spectra. Aside from that, through GC-MS analysis, dried orange-infused used cooking oil was discovered to have the highest percentage content of major antimicrobial compounds such as esters, oxygenated monoterpenoids, triterpenes, and alkaloids with 1.92% of the total amount of compounds found in the sample. However, the agar plate method revealed that the fresh lemon waste-infused used cooking oil disinfectant formulation was the most effective at inhibiting bacterial growth as the colony-forming detected on the agar plates dropped from 20 colonies to nearly zero and from 49 to 3 colonies for the plate swabbed with microbes from the table and doorknob surfaces, respectively. Based on the findings, the citrus waste and used cooking oil were viewed to have the potential as one of the possible ingredients in creating safer disinfectants in the future.